Stratification tools for assessing older adults with multimorbidity in an integrated care context: A scoping review - Jon André Christensen; Michael Marcussen; Vicki Zabell; Bettan Bagger; Ditte Høgsgaard; Sanne Lykke Lundstrøm; Barbara Ann Barrett; Anne Frølich; Søren Thorgaard Skou; Lene Lauge Berring (Journal of Multimorbidity and Comorbidity)
Background Older adults with multimorbidity experience fragmentation of care. Ensuring optimal use of healthcare services requires stratifying their need for integrated care. We aimed to map existing stratification tools for assessing older adults with multimorbidity in an integrated care context. Methods We searched MEDLINE, Embase, PsycINFO, Cochrane Library, and CINAHL, and extracted definitions of population, concept, and context following the JBI Framework for Scoping Reviews. Results We identified 17,689 articles of which 11 articles were included. Few stratification tools for this population exist and differ on scoring methods, domains and settings of use. Stratification is used for identifying older adults with multimorbidity to multidisciplinary teams or to case managers. Future research should develop stratification tools across sectors focused on the common risk factors of multimorbidity in older adults.